Explaining the Effects of the Rose Festival from the Perspective of Local Residents A Case Study of Kashan - Sedighe Kiani Salmi; Mohammad Reza Boshagh (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2016)
Traditionally, the impacts of tourism can be studied as the social, cultural, economic and environmental impacts. The aim of this study is to provide a model to explain the effects of Rose festival in the county of Kashan. The sample size was calculated based on Cochran method as 200. To analyze the data, SPSS22 and AMOS22 were used. The results indicate that, the Rose festival affected in terms of environmental, physical, social and economic. Economic factors, is dedicated as playing the most important role in explaining the effects of Rose festival. Another important factor is the environmental factor that is influenced by Rose Festival and the development of tourism. This factor is accounted for the largest number of variables. Another important factor that is influenced by development of tourism and the Rose Festival is the physicalfactor. The last factor is social. Being of a minimum load factor compares to other factors indicates that the social texture of Kashan resist against change and this area still retains its local identity.